ALPHAVIRUSES: MOLECULAR BIOLOGY AND PRACTICAL APPLICATIONS - Voikov , M.; Baltabekova , A.; Zhienbay , Ye.; Shustov , A. (Eurasian Journal of Applied Biotechnology, 2015)
Alphaviruses are enveloped viruses with positive sense RNA genomes, which replicate in the cytoplasm and have no DNA stage in their life cycle. They are natural infection agents of wild and domestic animals, and may also cause epidemics in humans who are dead-end hosts. Alphaviruses have small genomes and show active replication accompanied by the synthesis of large amounts of viral proteins. Representatives of this genus are able to infect many vertebrate and invertebrate cells. Since the genomic RNA of alphaviruses is infectious, viral progeny can be obtained by transfecting in vitro synthesized RNAs into cell culture, thus facilitating genetic engineering. Alphaviruses are attractive vectors for the production of recombinant proteins in cultured cells of mammals, birds, and invertebrates due to high levels of protein expression. Model viruses used for the development of alphavirus expression systems include the Sindbis virus, Venezuelan equine encephalomyelitis virus, and Semliki Forest virus. Use of wild-type alphaviruses as vectors is avoided because of their strong cytopathic effect in cell culture. Hence, numerous mutant alphaviral genomes with reduced cytopathic effect have been developed. Alphavirus vectors induce stronger cellular and humoral immune responses than other viral vectors, and therefore are used for the construction of live vaccines against infectious and non-infectious diseases (i.e. anti-cancer therapeutic vaccines). The wide cell and tissue tropism allows utilization of alphaviruses as agents for gene delivery under in vivo conditions and gene therapy.